The Impact of Organizational Reform on the Operational Performance of Taiwan’s Commercial Bank: Assessment Using the Camels Rating System - Liu Ying-Sing (ECONOMICS)
This study analyzed the impact of organizational reform on the operational performance of commercial banks. Furthermore, it examined the long-term effectiveness of the organizational reforms carried out by financial holding companies in their commercial banks from the perspective of individual enterprises. A case study examines the results of organizational change driven by the Commercial Bank, the first listed financial holding company in Taiwan, since 2006 to strengthen organizational execution. The study period is from the first quarter of 2000 to the first quarter of 2024, for a total of 97 quarters. The CAMELS Rating System evaluated banks’ operating performance, considering the board size factor, the stability of key insider positions, the asset size, and the impact of major infectious disease events (SARS and COVID-19). Modeling analysis was performed via stepwise regression. The empirical results show that organizational reforms can have a significant effect on banks’ capital adequacy, asset quality, management quality, liquidity, and sensitivity to market risk. Therefore, it is believed that organizational reform has the effects of sound assets, management quality, and reduced operational risk for banks. Major infectious disease events have a significant and priori-tized impact on banks’ capital adequacy and sensitivity. Additionally, banks’ operational performance has asset- and board-size effects. Finally, the results of this study can provide a reference for the internal organizational reform of financial institutions after mergers and acquisitions in the future.